Electroconvulsive Therapy: Attitudes and Practice of Iraqi Psychiatrists - Al-Hasnawi, Saleh M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Although Electroconvulsive Therapy (ECT) is still regarded as a controversial treatment by some people, it is an important and effective treatment. The practice of ECT is different across the world.Objectives: to obtain an overview of the electroconvulsive therapy   practice in Iraq.Method: Forty item self administered questionnaire about the attitude and practice of ECT, was sent (by mail or delivered by the researcher) to 73 Iraqi psychiatrists during the period from March to September, 2007.Results: Half of participants had asked for the patient's consent, and all asked the family for the consent,    72% had asked for written consent and 28% for oral consent only.  Majority ( 81%) gave oral  information to patient's family before ECT while 36% gave oral  information to patients .Average number of ECTs administered per patient were six, 61% perform ECT thrice weekly while 39% twice weekly. Maintenance ECT was used by 16% of participants. Bilateral ECT is exclusively used in Iraq and 74% perform unmodified ECT. Vast majority of the participants (85%) believed in application of ECT as a strongly effective treatment. The majority 79% never stop medications before ECT. Forty eight percent did routine investigations before ECT performance, The main complications associated with ECT were; amnesia (57%) headache (54%), and nine deaths were reported during the practice of the 65 psychiatrists. The main indications for ECT were depression (31%), schizophrenia  (26%)  , mania (21%) and schizoaffective(16%). Many absolute contraindication mentioned by Iraqi psychiatrists , increased intracranial pressure(79%) , space occupying lesions(74%), Myocardial infarction (64%), aortic aneurysm (56%) and below 15 years of age (41%)   Conclusion:  Iraqi psychiatrists practice of ECT is a mixture of different international experiences .A legislation and a code of practice for the use of  ECT is mandatory .